All The Light We Cannot See - Doerr, Anthony 1973-; Appelman, Zach.; Simon & Schuster Audio (Firm) ([New York] : Simon & Schuster Audio, 2014)
Marie Laure lives with her father in Paris and is blind by age six. Her father builds her a model of their neighborhood, so she can memorize it and navigate the real streets. When the Germans occupy Paris, they flee to Saint-Malo on the coast. In Germany, Werner grows up enchanted by a crude radio he finds. He becomes a master at building and fixing radios, which wins him a place with the Hitler Youth. Werner travels throughout Europe, and finally to Saint-Malo, where his meets Marie Laure.
Keywords: Blind -- Fiction; World War, 1939-1945 -- Fiction -- Youth -- France; World War, 1939-1945 -- Fiction -- Youth -- Germany; France -- Fiction -- History -- German occupation, 1940-1945; Saint-Malo (France) -- Fiction; Audiobooks